2023
DOI: 10.3390/microorganisms11020344
|View full text |Cite
|
Sign up to set email alerts
|

The Diversity of Escherichia coli Pathotypes and Vaccination Strategies against This Versatile Bacterial Pathogen

Abstract: Escherichia coli (E. coli) is a gram-negative bacillus and resident of the normal intestinal microbiota. However, some E. coli strains can cause diseases in humans, other mammals and birds ranging from intestinal infections, for example, diarrhea and dysentery, to extraintestinal infections, such as urinary tract infections, respiratory tract infections, meningitis, and sepsis. In terms of morbidity and mortality, pathogenic E. coli has a great impact on public health, with an economic cost of several billion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(44 citation statements)
references
References 502 publications
(508 reference statements)
1
21
0
Order By: Relevance
“…22 Once inside the host, bacteria can invade and multiply in various tissues and organs, leading to localized or systemic infections. 23 Viruses, on the other hand, require host cells to replicate. 24 They invade host cells and hijack their F I G U R E 1 Infectious agents, including bacteria, viruses, fungi, protozoa, and parasites, cause diseases in humans through respiratory droplets, contaminated food, insect bites, sexual contact, and direct contact with infected individuals or surfaces.…”
Section: Infectious Agentsmentioning
confidence: 99%
See 1 more Smart Citation
“…22 Once inside the host, bacteria can invade and multiply in various tissues and organs, leading to localized or systemic infections. 23 Viruses, on the other hand, require host cells to replicate. 24 They invade host cells and hijack their F I G U R E 1 Infectious agents, including bacteria, viruses, fungi, protozoa, and parasites, cause diseases in humans through respiratory droplets, contaminated food, insect bites, sexual contact, and direct contact with infected individuals or surfaces.…”
Section: Infectious Agentsmentioning
confidence: 99%
“…For bacteria, infection typically occurs through direct contact with contaminated surfaces or through the inhalation of respiratory droplets 22 . Once inside the host, bacteria can invade and multiply in various tissues and organs, leading to localized or systemic infections 23 . Viruses, on the other hand, require host cells to replicate 24 .…”
Section: Infectious Disease Outbreaksmentioning
confidence: 99%
“…4–6 Of the over 200 known serotypes of EHEC, EHEC is the primary cause of severe foodborne illnesses, whereas O157:H7 is responsible for the majority of foodborne outbreaks. 7,8 ETEC is responsible for approximately 220 million cases of diarrhea worldwide, with 75 million cases affecting children under 5 years of age. 9 And ETEC infections are a leading cause of traveler's diarrhea, resulting in over 400 000 global cases annually.…”
Section: Introductionmentioning
confidence: 99%
“…The World Health Organization (WHO) report in 2019, recognized E. coli as one of the bacteria that cause most diarrheal disease outbreaks, especially in areas with inadequate sanitation and safe water for domestic use. It has been reported that diarrheal disease is responsible for 370,000 children's annual mortality worldwide (Pokharel et al, 2023). In addition, E. coli causes peritonitis, pneumonia, urinary tract infections (UTIs), and urinary bacteremia (Fan et al, 2023;Sinnott-Stutzman & Sykes, 2021).…”
Section: Introductionmentioning
confidence: 99%